2002
DOI: 10.1002/ajmg.10149
|View full text |Cite
|
Sign up to set email alerts
|

Association of DRD4 in children with ADHD and comorbid conduct problems

Abstract: Recent family and twin study findings suggest that ADHD when comorbid with conduct problems may represent a particularly familial and heritable form of ADHD. Although several independent groups have shown association between the DRD4 7 repeat allele and ADHD, others have failed to replicate this finding. Previous TDT analyses of UK and Eire samples had also been negative. We set out to further examine the role of DRD4 but selecting a subgroup of children with ADHD and comorbid conduct problems. Families were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 27 publications
9
59
0
6
Order By: Relevance
“…However, as all Ôcases' met diagnostic criteria for ADHD at baseline, they also all had high ADHD symptom counts in childhood (at baseline). Therefore, the range for the number of symptoms was restricted (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). By adolescence, the variation in symptom scores was much greater (range 0-18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as all Ôcases' met diagnostic criteria for ADHD at baseline, they also all had high ADHD symptom counts in childhood (at baseline). Therefore, the range for the number of symptoms was restricted (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). By adolescence, the variation in symptom scores was much greater (range 0-18).…”
Section: Discussionmentioning
confidence: 99%
“…To improve the accuracy of retrospective phenotypic measurement, participants who had been taking stimulant medication for more than a year were excluded. More detail on the original crosssectional study and its findings can be found in Holmes et al [18], Langley et al [21] and Whittinger et al [37]. The baseline genetic data have since been expanded due to additional genotyping.…”
Section: Methodsmentioning
confidence: 99%
“…Faraone (2000) 16 has suggested that ADHD with conduct disorder may represent a sub-type with increased familial loading and this has been supported by recent twin evidence. 22 Holmes et al 23 combined all the UK and Irish studies looking at children with ADHD and conduct disorder symptoms. Despite previous findings of a lack of an association between DRD4 7 repeat allele and ADHD using the TDT, for 67 children who fulfilled diagnostic criteria for ADHD and displayed conduct disorder symptoms, evidence of an association between DRD4 and ADHD with 'conduct problems' was found (7 repeat allele-24 transmissions, 13 non-transmissions; P = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In a joint analysis of data from the UK and Eire, the subgroup of ADHD with CD was significantly associated with the DRD4 7 repeat allele, 46 whereas association was not detected in the full ADHD sample. That this is a genuine rather than chance finding is supported by similar observations in a follow-up study in an expanded Irish sample.…”
Section: Comorbiditymentioning
confidence: 93%